Downhill racer - Hall, Oakley M. 1920-2008; Hopkins, Kenyon 1912-1983 (The Criterion collection, 2009)
"Ein ehrgeiziger Sportler ohne Mannschaftsgeist wird bis zum Olympiasieg aufgebaut. Er gewinnt die Goldmedaille und kann sich auch menschlich bewähren. Der Film bietet faszinierende Aufnahmen von Ski-Abfahrten und eine große Starbesetzung, [...]"
1.85:1 aspect ratio
Orig.: USA 1969
Enth. special edition features: New, restored high-definition digital transfer. - New video interviews with Robert Redford, screenwriter James Salter, film editor Richard Harris, production manager Walter Coblenz, and former downhill skier Joe Jay Jalbert, who served as a technical adviser, ski double and cameraman ; audio excerpts from a 1977 American Film Institute seminar with director Michael Ritchie ; "How Fast?", a rare, 12-minute promotional featurette. Theatrical Trailer ; a booklet featuring an essay by critic Todd McCarthy.